Design rules for efficient transgene expression in plants. Issue 7 (23rd May 2014) - Jackson, Mark A.; Sternes, Peter R.; Mudge, Stephen R.; Graham, Michael W.; Birch, Robert G.
Summary Sustained expression of transgenes in specified developmental patterns is commonly needed in plant biotechnology, but obstructed by transgene silencing. Here, we present a set of gene design rules, tested on the silencing‐susceptible beetle luc and bacterial ims genes, expressed in sugarcane. Designs tested independently or in combination included removal of rare codons, removal of RNA instability sequences, blocking of likely endogenous sRNA binding sites and randomization of non‐rare codons. Stable transgene expression analyses, on multiple independent lines per construct, showed greatest improvement from the removal of RNA instability sequences, accompanied by greatly reduced transcript degradation evident in northern blot analysis. We provide a set of motifs that readily can be eliminated concurrently with rare codons and undesired structural features such as repeat sequences, using Gene Designer 2.0 software. These design rules yielded 935‐ and 5‐fold increased expression in transgenic callus, relative to the native luc and ims sequences; and gave sustained expression under the control of sugarcane and heterologous promoters over several years in greenhouse and field trials. The rules can be applied easily with codon usage tables from any plant species, providing a simple and effective means to achieve sustained expression of otherwise silencing‐prone transgenes in plants.